2020
DOI: 10.1126/sciadv.aba6038
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical decoupling of quantum emitters in hexagonal boron nitride from low-energy phonon modes

Abstract: Quantum emitters in hexagonal boron nitride were recently reported to hold unusual narrow homogeneous linewidths of tens of megahertz within the Fourier transform limit at room temperature. This unique observation was traced back to decoupling from in-plane phonon modes. Here, we investigate the origins for the mechanical decoupling. New sample preparation improved spectral diffusion, which allowed us to reveal a gap in the electron-phonon spectral density for low phonon frequencies. This sign for mechanical d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 52 publications
(61 reference statements)
4
57
1
Order By: Relevance
“…A remedy to these limitations may be provided by recently discovered defects in layered materials. One of the most prominent stackable 2D materials is hexagonal boron nitride (hBN) which hosts a large variety of atom-like defects including single-photon emitters 11 14 . Spin carrying defects have been theoretically predicted and experimentally confirmed in hBN 15 – 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A remedy to these limitations may be provided by recently discovered defects in layered materials. One of the most prominent stackable 2D materials is hexagonal boron nitride (hBN) which hosts a large variety of atom-like defects including single-photon emitters 11 14 . Spin carrying defects have been theoretically predicted and experimentally confirmed in hBN 15 – 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study shows that the observed PSB can be explained by coupling to bulk longitudinal optical (LO) phonons, and the asymmetric ZPL by additional longitudinal acoustic phonons (LA) as well as local modes [89]. The electronoptical-phonon sideband of the excited state can be investigated by PLE measurements, where resonant driving of the phonon resonances discloses the coupling of individual modes [19,88]. Investigations on the emitter's coupling efficiency to different phonon modes by means of PLE measurements demonstrates that the excitation mediated by the absorption of one in-plane optical phonon increases the emitter absorption probability by a factor of 10 as compared to that mediated by acoustic or out-of-plane optical phonons [88].…”
Section: Electron-phonon Couplingmentioning
confidence: 99%
“…DOI: /10.1364/OPTICA.6.000542 a two-dimensional material could play a key role to overcome the requirements for sample cooling. The orbitals of hosted defect centers could be oriented in a mechanically isolated way such that optical transitions remain decoupled from phonon interactions of relevant phonon modes [19]. Although the exact orbital structure that enables the isolation is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] This class of materials is of a particular interest as their layered nature provides avenues for nanoscale manipulation and reliable integration with photonic devices. [ 4 ] hBN SPEs are especially promising due to the stability of the host, [ 5 ] room temperature operation, [ 6 ] outstanding optical properties, [ 7 ] and the presence of optically detected magnetic resonance signals. [ 8 ]…”
Section: Figurementioning
confidence: 99%
“…3,4 This class of materials is of a particular interest as their layered nature provides avenues for nanoscale manipulation and reliable integration with photonic devices. [5][6][7][8] hBN SPEs are especially promising due to the stability of the host, 9 room temperature operation, 10 outstanding optical properties, 11 and the presence of optically detected magnetic resonance signals. [12][13][14] SPEs in hBN can be engineered through chemical vapor deposition (CVD), [15][16][17] molecular beam epitaxy, 12,18 or metal organic vapor phase epitaxy.…”
Section: Introductionmentioning
confidence: 99%